(untitled) (Journal of Experimental and Clinical Anatomy, 2024)
BACKGROUNDAND AIM: Male infertility is a significant global health concern, with sperm quality deficiencies contributing significantly to its prevalence. Infertility affects approximately 15% of couples globally, with male factors contributing to around 50% of cases. Medicinal plants, including the African walnut (Plukenetia conophora), are gaining attention for their potential in addressing reproductive health challenges. The aim of this study was to evaluate protective effects of ethanol seed extract of Plukenetia conophora (African walnut) on cadmium-induced reproductive toxicity in male Wistar rats. METHODS: Thirty-six adult male Wistar Rats were divided into six groups and subjected to different treatments, group A served as the control group, Group B and C received 250 mg/kg body weight and 500 mg/kg body weight of ethanol seed extract of Plukenetia conophora only respectively, group D and E received 250 mg/kg body weight and 500 mg/kg body weight of Plukenetia conophora in addition to 10mg/kg body weight of cadmium chloride respectively, and group F received 10 mg/kg body weight of cadmium chloride only over a 56-day period, Cadmium and Plukenetia conophora were administered daily using orogastric tube. RESULTS: Cadmium chloride negatively impacts body weight, testicular weight, and sperm quality. Plukenetia conophora extract exhibits protective effects, mitigating the detrimental impact of cadmium, particularly at lower doses. Histological analysis confirmed the protective role of the extract in maintaining normal testicular architecture. CONCLUSION: Plukenetia conophora extract shows potential as a protective agent against cadmium-induced reproductive toxicity, highlighting its therapeutic potential for male infertility caused by environmental toxins. Further research is warranted to explore its clinical applications.